Analysis of The Effect of Macro Economic Factors on Indonesian Export Value Fluctuation (Empirical Data in Period: 1990 To 2018) - R. , Roosaleh Laksono (International Journal of Psychosocial Rehabilitation, 2020)
An export is a source of foreign exchange for a country that must be considered and sought as much as possible and as widely as possible by the government. This study aims to determine whether macroeconomic factors, especially the real exchange rate (rupiah against the USD), investment, and inflation affect the value of exports in Indonesia, both long-term and short-term, during the period 1990 to 2018. Research previously produced has gone through several stages of statistical testing. The results of research that have been done show that there has been an equilibrium long-run relationship between these macroeconomic factors and fluctuations in Indonesia's export value; this is evidenced through several stages of statistical tests, but conversely, there is no disequilibrium in sort-run relationships, meaning value, real exchange, investment, and inflation have no effect on the short-run relationship to the value of exports; this is evidenced through the results of the cointegration test and error correction method (ECM) test, where all variable data are not stationary and not cointegration, and the results show are not significant.